Urban Remote Sensing - Weng, Qihao; Quattrochi, Dale; Gamba, Paolo E.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Urban Remote Sensing, Second Edition assembles a team of professional experts to provide a much-needed update on the applications of remote sensing technology to urban and suburban areas. This book reflects new developments in spaceborne and airborne sensors, image processing methods and techniques, and wider applications of urban remote sensing to meet societal and economic challenges. In various sections of the book the authors address methods for upscaling urban feature extraction to the global scale, new methods in mapping and detecting urban landscape features and structures, and mapping and monitoring urbanization in developing countries. Additionally, readers are provided with valuable case studies such as the HEAT (Heat Energy Assessment Technologies) project in Calgary, Canada and the use of VHR (very high resolution) satellite monitoring in Salzburg, Austria to tackle challenges of urban green planning. Features Explores the most up-to-date developments in the field of urban remote sensing Integrates both technical and practical aspects covering all different topics of global urban growth issues Provides new and updated contributions addressing data mining of remotely sensed big data, recent urban studies on a global scale, accuracy assessment and validation, and new technical challenges Examines various applications of urban remote sensing in support of urban planning, environmental management, and sustainable urban development. Authors are renowned figures in the field of remote sensing
Part I Data, Sensors, and Systems Considerations and Algorithms for Urban Feature Extraction. -- The Global Urban Footprint. -- Thomas Esch, Wieke Heldens, and Andreas Hirner -- Development of On-Demand Human Settlement Mapping System using Historical Satellite Archives. -- Hiroyuki Miyazaki and Ryosuke Shibasaki -- Morphological Building Index (MBI) and Its Applications to Urban Areas. -- Xin Huang and Tao Zhang -- Part II Assessing and modeling urban landscape compositions, patterns and structures. -- Stereo-Based Building Roof Mapping in Urban Off-Nadir VHR Satellite Images: Challenges and Solutions. -- Alaeldin Suliman and Yun Zhang -- Beyond Built-Up: The Internal Makeup of Urban Areas. -- Benjamin Bechtel, Martino Pesaresi, Aneta J. Florczyk, and Gerald Mills -- Urban Change Detection Utilizing High Resolution Optical Images Taken from Different Viewing-Angles and Different Platforms. -- Shabnam Jabari and Yun Zhang -- Part III Monitoring, analyzing, and modeling urban growth. -- Urbanisation in India: Patterns, Visualisation of Cities and Greenhouse Gas Inventory for Developing an Urban Observatory. -- Bharath Haridas Aithal, Maysore Chandrashekar Chandan, Shivamurthy Vinay, and T.V. Ramachandra -- Mapping Imperious Surface in the Greater Hanoi Area, Vietnam from Time Series Landsat Image, 1988 - 2015. -- Hung Q. Ha and Qihao Weng -- City in desert: Mapping subpixel urban impervious surface area in a desert environment using spectral unmixing and machine learning methods. -- Chengbin Deng and Weiying Lin -- Application of Remote Sensing and Cellular Automata Model to Analyze and Simulate Urban Density Changes. -- Santiago Linares and Natasha Picone -- Part IV Urban Planning and Socioeconomic Applications. -- Developing Multiscale HEAT Scores from H-Res Airborne Thermal Infrared Imagery to Support Urban Energy Efficiency: Challenges Moving Forward. -- Bharanidharan Hemachandran, Geoffrey J. Hay, Mir Mustafiz Rahman, Isabelle Couloigner, Yilong Zhang, Bilal Karim, Tak S. Fung, and Christopher D. Kyle -- Air Quality and Health Monitoring In Urban Areas Using EO and Clinical Data. -- Andrea Marinoni and Paolo Gamba -- Urban Green Mapping and Valuation. -- Stefan Lang, Thomas Blaschke, Gyula Kothencz, and Daniel Hlbling.
Includes bibliographical references and index.
Also available in print format.
Keywords: Airborne Lidar Data; Bayesian Spectral Mixture Analysis; Mapping Human Settlements; SAR imagery; urban areas; Sub-Pixel Analysis; Urban Landscapes; Urban Terrain; City planning -- Remote sensing; Land use, Urban -- Remote sensing; Urban geography -- Remote sensing; Electronic books